PENGARUH PARIWISATA TERHADAP PERTUMBUHAN EKONOMI DI KOTA SABANG - Shakhibul Amnar; Said Muhammad; Mohd Nur Syechalad (Syiah Kuala University, 2017)
This study aims to determine the effect of the number of foreign tourists, the number of tourists, the number of attractions and the number of hotel rooms / hotel occupancy rate on regional economic growth Sabang City. The data in this study using time series data in the period 1996 to 2015 with a sample of 20 years. The analysis model used is multiple regression (multiple linear regression) through Ordinary Least Squrae (OLS). The results showed that the number of foreign tourists, the number of tourists, the number of attractions and the number of hotel rooms / hotel occupancy rate positive and significant impact on regional economic growth Sabang City. Expected for policy makers to continue to improve the tourism sector, improve and add to the transportation facilities and improve local facilities so as to make tourists feel at home and want to come back to visit City of Sabang, increase the number of tourist sites and the promotion of the tourism sector to support economic growth in the city of Sabang.